1997 IEEE Ultrasonics Symposium Proceedings. An International Symposium (Cat. No.97CH36118)
DOI: 10.1109/ultsym.1997.663340
|View full text |Cite
|
Sign up to set email alerts
|

Single element and linear array PZT ultrasound biomicroscopy transducers

Abstract: PZT coatings have been produced in the thickness range of S-200 microns using a composite sol gel process high frequency transducers suitable for ultrasound [l]. The application of this process in the fabrication of biomicroscopy (UBM) has been investigated. Curved single element transducers have been produced in a range of 70-165MHz with -6dB bandwidths as high as 52% and minimum insertion losses ranging from -47 to -58dB. Laser micromachining techniques for patterning linear array smctures to operate at simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Lukacs et al [133] demonstrated that single element high frequency transducers could be fabricated with a composite sol–gel PZT film. The center frequency of the transducer is in range of 70–160 MHz, with −6 dB bandwidth of 16–52%.…”
Section: Piezoelectric High Frequency Films Devicesmentioning
confidence: 99%
“…Lukacs et al [133] demonstrated that single element high frequency transducers could be fabricated with a composite sol–gel PZT film. The center frequency of the transducer is in range of 70–160 MHz, with −6 dB bandwidth of 16–52%.…”
Section: Piezoelectric High Frequency Films Devicesmentioning
confidence: 99%
“…Lukacs et al [4] demonstrated that single element transducers could be fabricated from PZT thick film. They used a modified sol-gel PZT composite to fabricate high frequency ultrasound transducers from 70 to 160 MHz, but the bandwidths of the transducers were low (from 52% to 16% at À6 dB).…”
Section: Introductionmentioning
confidence: 99%
“…One of the common lead-based composites used in ultrasonic sensors is PZT/PZT, which has a wide range of center frequency from 17 to 160 MHz and a −6 dB bandwidth ranging from 14 to 37.5 MHz. PZT/PZT has been fabricated on various substrates including steel and aluminum [ 58 , 59 , 60 ]. BiT (Bismuth Titanate) has a high curie temperature of 675 °C and has been applied in a BiT/ PZT composite.…”
Section: High-temperature Ultrasonic Transducers (Htut) By Sol-gel Techniquementioning
confidence: 99%